Simulation of braking performance: The AnsaldoBreda EMU V250 application. (February 2015) - Pugi, Luca; Malvezzi, Monica; Papini, Susanna; Tesi, Simone
This paper presents the development of a modular tool for the prediction of train braking performance. Particular attention is devoted to the accurate prediction of stopping distances, considering different loading and operating conditions, necessary to verify safety requirements prescribed by the European Technical Specifications for Interoperability of High Speed Trains (TSI-HS) and the corresponding EN regulations. Results are verified by considering, as a benchmark, the AnsaldoBreda EMU V250: a European train being developed for Belgium and The Netherlands's high-speed lines. Technical information and experimental data were available for this train, directly recorded during preliminary supplier exercise. Validation results were encouraging, and allowed a more accurate identification of the pad friction factor influence on braking performance.